Tīna thora deśabhakta : Dādābhāī Naurojī, Ṭerensa Mêkasvinī, Di. Vhêlerā - Phadke, Narayan Sitaram (SAMP early 20th-century Indian books project, 1942)
Biographies of Dadabhai Naoroji, 1825-1917, Indian nationalist, Terence Joseph MacSwiney, 1879-1920, and Eamonn de Valera, 1882-1975, Irish nationalist and former president respectively.